Quantização de Landau para partículas neutras em anéis quânticos - Dantas, Lincoanderson Oliveira (2011)
In this work, we shall show that a Landau quantization analog is possible for neutral particles in two-dimensional quantum rings. For that we have used the Tan Inkson model for a quantum ring to confine neutral atoms in the ring. We have also used two different fields configurations to induce a electric dipole moment on the particle. In addition, we have made a review of some quantum effects, such that Aharonov-Bohm like effects and Landau quantization for neutral and charged particles.